The prolonged impact of COVID-19 on symptoms, health-related quality of life, fatigue and mental well-being: a cross-sectional study - Brus, Iris M.; Spronk, Inge; Haagsma, Juanita A.; de Groot, Annemieke; Tieleman, Peter; Biere-Rafi, Sara; Polinder, Suzanne (Frontiers in Epidemiology, 2023)
Background: A subset of patients experience persisting symptoms after an acute COVID-19 infection, referred to as “post COVID-19 condition”. This cross-sectional study aimed to compare symptoms, health-related quality of life (HRQoL), fatigue, mental well-being, and determinants of diminished HRQoL, between patients with post COVID-19 condition categorized by time since acute infection. Methods: We performed an online survey and analyzed responses of 10,194 adult respondents with a confirmed or suspected COVID-19 infection, who experienced persisting symptoms ≥3 months after the initial infection. The most debilitating symptoms and health outcomes were studied separately for respondents 3-6, 7-9, 10-12, 13-18, 19-24, and >24 months after acute infection. Results: At each time period, fatigue, sensory-processing problems, and concentration problems were the most debilitating symptoms reported by respondents, although the proportion of respondents who reported these symptoms differed significantly between time periods. Respondents 3-6 months post-acute infection had the lowest HRQoL (median EQ-5D utility score: 0.59), the highest fatigue level (median score: 110.0) and the highest proportion with a likely depressive disorder (32.4%), whereas respondents 13-18 months post-infection had the highest HRQoL (0.65), the lowest fatigue level (106.0), and the second lowest proportion with a likely depressive disorder (25.0%) (p=0.000-0.007). Compared to those 13-18 and 19-24 months post-infection, respondents >24 months post-infection had a slightly lower HRQoL (0.60), lower fatigue level (108.0), and lower proportion with a likely depressive disorder (29.2%), although only the differences in HRQoL were statistically significant (p=0.001-0.010). Younger age, female gender, lower level of education, not having paid work before COVID-19, comorbidity, and not being vaccinated, seemed to be associated with lower HRQoL. Conclusion: Regardless of time since infection, respondents considered fatigue, sensory processing problems and concentration problems the most debilitating symptoms. They experienced a low HRQoL and severe fatigue, even more than two years after acute COVID-19 infection. Respondents 3-6m post-infection had the worst health outcomes, whereas respondents 13-18m post-infection had the best outcomes, indicating that, at least for a subgroup of patients, health status may improve over time.